Innovation capability in SMEs: A systematic review of the literature - Minna Saunila (Journal of Innovation & Knowledge (JIK), 2020)
Despite the profusion of innovation reviews, there is lack of reviews of innovation capability in small business context. There is a need to define the construct from a practical point of view by utilizing existing innovation research. Thus, this study aims to enhance the understanding about the characteristics of innovation capability in small business context by reviewing the empirical literature. This paper presents the results of a systematic review on the innovation capability in small businesses. As the main contribution, the paper identifies a holistic view of the evolving research on innovation capability in small businesses. Thus, the paper draws a picture of the topics investigated in the literature, and provides an understanding about the different communities of innovation capability research. There are no prior systematic literature reviews on innovation capability in small businesses. The results enhance understanding about the special characteristics of innovation capability in small business context. The presented characterization of innovation capability can guide further studies by offering precepts for how innovation capability can be comprehended among small businesses. Further, using the findings of this review, managers can improve their firms' capability to innovate by acknowledging the multiple facets of innovation capability.
Keywords: 650; Innovation; Innovation capability; Innovation outcome; Innovation performance; Innovation process; Performance; Performance management; SME; Systematic review